Cancer survival among World Trade Center rescue and recovery workers: A collaborative cohort study. Issue 10 (19th July 2021) - Goldfarb, David G.; Zeig‐Owens, Rachel; Kristjansson, Dana; Li, Jiehui; Brackbill, Robert M.; Farfel, Mark R.; Cone, James E.; Kahn, Amy R.; Qiao, Baozhen; Schymura, Maria J.; Webber, Mayris P.; Dasaro, Christopher R.; et al.
Abstract: Background: World Trade Center (WTC)‐exposed responders may be eligible to receive no‐cost medical monitoring and treatment for certified conditions, including cancer. The survival of responders with cancer has not previously been investigated. Methods: This study compared the estimated relative survival of WTC‐exposed responders who developed cancer while enrolled in two WTC medical monitoring and treatment programs in New York City (WTC‐MMTP responders) and WTC‐exposed responders not enrolled (WTC‐non‐MMTP responders) to non‐responders from New York State (NYS‐non‐responders), all restricted to the 11‐southernmost NYS counties, where most responders resided. Parametric survival models estimated cancer‐specific and all‐cause mortality. Follow‐up ended at death or on December 31, 2016. Results: From January 1, 2005 to December 31, 2016, there were 2, 037 cancer cases and 303 deaths (248 cancer‐related deaths) among WTC‐MMTP responders, 564 cancer cases, and 143 deaths (106 cancer‐related deaths) among WTC‐non‐MMTP responders, and 574, 075 cancer cases and 224, 040 deaths (158, 645 cancer‐related deaths) among the NYS‐non‐responder population. Comparing WTC‐MMTP responders with NYS‐non‐responders, the cancer‐specific mortality hazard ratio (HR) was 0.72 (95% confidence interval [CI] = 0.64–0.82), and all‐cause mortality HR was 0.64 (95% CI = 0.58–0.72). The cancer‐specific HR was 0.94 (95% CI = 0.78–1.14), and all‐cause mortality HR was 0.93 (95% CI = 0.79–1.10) comparing WTC‐non‐MMTP responders to the NYS‐non‐responder population. Conclusions: WTC‐MMTP responders had lower mortality compared with NYS‐non‐responders, after controlling for demographic factors and temporal trends. There may be survival benefits from no‐out‐of‐pocket‐cost medical care which could have important implications for healthcare policy, however, other occupational and socioeconomic factors could have contributed to some of the observed survival advantage.